Fatal Electrical Injuries in Padang, Indonesia: A Medicolegal Investigation of Circumstances and Cause of Death - Fauzi, Irman (Sriwijaya Journal of Forensic and Medicolegal, 2023)
Introduction: Electrical injuries, particularly those leading to fatalities, present significant public health concerns globally. In Indonesia, the incidence of electrical injuries remains a pressing issue, necessitating in-depth medicolegal investigations to understand the circumstances surrounding these deaths and contribute to preventive strategies. This study aimed to analyze fatal electrical injury cases in Padang, Indonesia, focusing on the demographic characteristics of victims, circumstances of the incidents, autopsy findings, and cause of death determination. Methods: A retrospective review of medicolegal autopsy reports from the Forensic Medicine Department in Padang, Indonesia, was conducted between 2018 and 2023. Cases involving fatal electrical injuries were identified and analyzed for demographic data, scene investigation details, autopsy findings, and cause of death. Descriptive statistics were used to summarize the data. Results: A total of 78 cases of fatal electrical injuries were identified. The majority of victims were males (87.2%) with a mean age of 35.2 years. Most incidents occurred in occupational settings (56.4%), followed by domestic environments (34.6%). Low-voltage electrocutions were predominant (83.3%). Common autopsy findings included electrical burns (94.9%), internal organ damage (42.3%), and histological evidence of electrocution (64.1%). The cause of death was primarily attributed to ventricular fibrillation (53.8%) and respiratory arrest (28.2%). Conclusion: Fatal electrical injuries in Padang, Indonesia, disproportionately affect males in occupational settings. Low-voltage electrocutions remain a major concern. Medicolegal investigations play a crucial role in understanding the circumstances and cause of death in these cases, aiding in the development of targeted preventive measures and safety regulations to reduce the incidence of such fatalities.